The Story of a Mine - Harte, Bret, 1836-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Story of a Mine" by Bret Harte is a novel written during the late 19th century. The narrative revolves around Concho, a Mexican prospector navigating the challenging landscape in search of silver and gold, as well as the darker human motivations intertwined with such pursuits. The story introduces themes of greed, deception, and the moral complexities of men driven by avarice against the backdrop of the rugged California wilderness. At the start of the novel, we meet Concho as he struggles along a steep trail in search of fortune, feeling defeated and exhausted. After a mishap with his mule, he encounters a stranger named Mr. Joseph Wiles, who claims to be a metallurgist. They engage in a conversation about the potential silver that could be found in a lump of ore Concho possesses, which stirs his excitement and suggests a profitable future. However, as the narrative unfolds, it becomes evident that Wiles represents a more sinister side of prospecting, hinting at manipulation and betrayal. Concho's naive trust in Wiles sets the stage for a deeper exploration of greed and deception that drives the plot forward. (This is an automatically generated summary.)
Release date is 2006-05-22
Produced by Donald Lainson; An Anonymous Volunteer; David Widger
Keywords: American fiction -- 19th century; Mines and mineral resources -- Fiction